Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's determine the series of transformations needed to change the original vertices [tex]\( B(-3,0), C(2,-1), D(-1,2) \)[/tex] into the new vertices. We will break this down step by step.
The goal is to achieve the transformed vertices:
[tex]\[ B'(5,2), C'(0,1), D'(3,4) \][/tex]
The transformations to be considered are:
1. Reflection over the y-axis: This involves changing the sign of the x-coordinate.
2. Translation: This involves adjusting the coordinates by adding or subtracting a fixed value to the x and y coordinates.
Let's start by reflecting each vertex over the y-axis.
Original vertices:
- [tex]\( B(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \)[/tex]
- [tex]\( D(-1, 2) \)[/tex]
Step 1: Reflect over the y-axis
- [tex]\( B(-3, 0) \rightarrow (3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow (-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow (1, 2) \)[/tex]
Now, the intermediate vertices after reflection are:
- [tex]\( B_{\text{reflected}}(3, 0) \)[/tex]
- [tex]\( C_{\text{reflected}}(-2, -1) \)[/tex]
- [tex]\( D_{\text{reflected}}(1, 2) \)[/tex]
Step 2: Translate (x, y) to (x+2, y+2)
- [tex]\( B_{\text{reflected}}(3, 0) \rightarrow (3+2, 0+2) = (5, 2) \)[/tex]
- [tex]\( C_{\text{reflected}}(-2, -1) \rightarrow (-2+2, -1+2) = (0, 1) \)[/tex]
- [tex]\( D_{\text{reflected}}(1, 2) \rightarrow (1+2, 2+2) = (3, 4) \)[/tex]
So, the final transformed vertices are:
- [tex]\( B'(5, 2) \)[/tex]
- [tex]\( C'(0, 1) \)[/tex]
- [tex]\( D'(3, 4) \)[/tex]
These are the desired vertices. Therefore, the correct series of transformations is:
[tex]\[ (x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{(x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2)} \][/tex]
The goal is to achieve the transformed vertices:
[tex]\[ B'(5,2), C'(0,1), D'(3,4) \][/tex]
The transformations to be considered are:
1. Reflection over the y-axis: This involves changing the sign of the x-coordinate.
2. Translation: This involves adjusting the coordinates by adding or subtracting a fixed value to the x and y coordinates.
Let's start by reflecting each vertex over the y-axis.
Original vertices:
- [tex]\( B(-3, 0) \)[/tex]
- [tex]\( C(2, -1) \)[/tex]
- [tex]\( D(-1, 2) \)[/tex]
Step 1: Reflect over the y-axis
- [tex]\( B(-3, 0) \rightarrow (3, 0) \)[/tex]
- [tex]\( C(2, -1) \rightarrow (-2, -1) \)[/tex]
- [tex]\( D(-1, 2) \rightarrow (1, 2) \)[/tex]
Now, the intermediate vertices after reflection are:
- [tex]\( B_{\text{reflected}}(3, 0) \)[/tex]
- [tex]\( C_{\text{reflected}}(-2, -1) \)[/tex]
- [tex]\( D_{\text{reflected}}(1, 2) \)[/tex]
Step 2: Translate (x, y) to (x+2, y+2)
- [tex]\( B_{\text{reflected}}(3, 0) \rightarrow (3+2, 0+2) = (5, 2) \)[/tex]
- [tex]\( C_{\text{reflected}}(-2, -1) \rightarrow (-2+2, -1+2) = (0, 1) \)[/tex]
- [tex]\( D_{\text{reflected}}(1, 2) \rightarrow (1+2, 2+2) = (3, 4) \)[/tex]
So, the final transformed vertices are:
- [tex]\( B'(5, 2) \)[/tex]
- [tex]\( C'(0, 1) \)[/tex]
- [tex]\( D'(3, 4) \)[/tex]
These are the desired vertices. Therefore, the correct series of transformations is:
[tex]\[ (x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2) \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{(x, y) \rightarrow (-x, y) \rightarrow (x+2, y+2)} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.